SISTEM DAN PROSEDUR PIUTANG DAGANG PADA PT. AUTO MOBIL BORNEO PERDANA (HINO) CABANG SINTANG - B41111098, Gita Pratiwi gita (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
GITA PRATIWI B41111098 ABSTRACT The problem that will be examined in this research is about account receivable of PT. HINO, Sintang Branch. The aim of this research is to know the view about the account receivable system and procedure of PT. HINO, Sintang Branch, where the writer directly went to the factory to collect the data to learn about the system and procedure in sales on credit based on the real facts. The methods used to collect the data are observation and interview. The data then been analyzed with primaryband secondary data, while the instruments of analysis used in this research the structure of organization analysis, flowchart analysis, complience test analysis, and questionnaire analysis. The result of this research shows that the system and procedure on account receivable in PT.HINO has been quite good but there is still a deficiency in sales on credit due to less accurate in evaluating consumer applicant. The conditions on credit become incomplete and inappropriate that can cause stuck in consumer payment every month. Some advices given are PT. HINO should be more accurate in evaluating consumer applicant and recruit more employees in collector division so the monthly payment will be claimed and covered. Keywords : System, Procedure, Account Receivable Â